Effect of extracts, leachates and washings from potato virus X infected potato leaves on aggressiveness of Alternaria solani - S.M. PAUL KHURANA; B.P. SINGH2, A. KALRA1*, R.K. GROVERI1, N. RISHI1, (Indian Phytopathology, 2002)
The influence of potato virus X (PVX) infection on the germination of Alternaria solani spores and its aggressiveness was investigated in vitro. Extracts, leachates and washings from PVX-infected potato (cv. Kufri Chandramukhi) leaves suppressed thegermination of A. solani spores. Likewise, aggressiveness of A. solani was also reduced as the lesions formed on potato leaves were fewer and smaller when A. solani spores were mixed with extracts, leachates and washings from PVX-infected leaves in comparison with A. solani spores alone. Increased resistance of PVX infected leaves appeared to be related to fungitoxic compounds produced on or near the surface of the leaves.